Immunocomplexes and tumour growth.Detection of immunocomplexes in high and low malignant tumour sublines (Revista Española de Fisiología, 1981)
Two different techniques to measure immunocomplexes on biological fluids are presented.The first one is based on the inhibition of the antibody dependent cell cytotoxicity (ADCC).A competition is established between immunocomplexes and the rabbit anti chicken antibodies bound to chicken red blood cells for the Fc receptors of K cells.The second technique detects the presence of immunocomplexes by the inhibition of the cytotoxicity on a haemolytic system as a result of the consumption of the complement.Both techniques were performed in parallel to compare their sensitivity.The presence of immunocomplexes in the ascites of tumour bearing mice has been demonstrated with two highly related tumours (MCG4 O and MGC4 C) with different immunogenic properties.No immunocomplexes were detected in the serum of the same mice.